Entrepreneurial universities for science and technology: Cases of KAIST and POSTECH - Park, Mun-su; Jeong, Seung Ouk (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The entrepreneurial university concept is a new challenge and opportunity for science and technology (S&T) universities in Korea. The traditional university functions of education, research, and community service are still highly relevant, but increasingly so are new types of collaboration for research outcomes and funding resources. Strategic university management is needed to handle socioeconomic contribution, involving the creation and maintenance of proactive relationships with firms, national and regional governments, and other regional entities. The emergence of the entrepreneurial university in Korea is similar to the socioeconomic changes observable in the history of university development in America and in many other developed countries. In this paper, we examine the emerging paradigm of entrepreneurial universities in Korea and discuss the interactions among universities, firms, and government strategy and policy by investigating and comparing two universities, POSTECH and KAIST, in their leadership, adaptation to changes in the environment, business strategies, organization, and cooperative network. We conclude with policy points that emphasize the fact that while entrepreneurial universities are an emerging concept, they can expand innovation and creativity in education and research in Korean universities in the mid-to-long term if university administration, policymakers and public administrators, and regional innovation actors take an interest in the need for a new organization and system where university research can contribute socioeconomically.